2017
DOI: 10.1021/acscatal.7b02310
|View full text |Cite
|
Sign up to set email alerts
|

Size-Tunable Ni Nanoparticles Supported on Surface-Modified, Cage-Type Mesoporous Silica as Highly Active Catalysts for CO2 Hydrogenation

Abstract: In this study, ultrasmall Ni nanoparticles (Ni NPs) were controllably supported in the cage-type mesopores of −COOH-functionalized mesoporous silica SBA-16 (denoted as Ni­(x)@S16C, where x is the Ni loading) via wet impregnation under alkaline conditions, followed by thermal reduction. The particle sizes of the Ni NPs ranged from 2.7 to 4.7 nm, depending on the Ni loading. Under the appropriate alkaline conditions (i.e., pH 9) deprotonation of the carboxylic acid groups on the cage-type mesopore surfaces endow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(59 citation statements)
references
References 65 publications
2
57
0
Order By: Relevance
“…Catalysts 2019, 9, x FOR PEER REVIEW 2 of 11 surface area, such as mesoporous silica [16][17][18]. However, the metal loading of a catalyst prepared using this method is low, and usually not higher than 30 wt %.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalysts 2019, 9, x FOR PEER REVIEW 2 of 11 surface area, such as mesoporous silica [16][17][18]. However, the metal loading of a catalyst prepared using this method is low, and usually not higher than 30 wt %.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…To increase the low-temperature activity of Ni-based catalysts, many methods have been proposed for preparing catalysts with a small Ni particle size [15]. A general strategy for increasing the dispersion of active components involves loading the active component on a carrier with a high surface area, such as mesoporous silica [16][17][18]. However, the metal loading of a catalyst prepared using this method is low, and usually not higher than 30 wt %.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, low‐cost, highly efficient and sustainable catalysts for methanol synthesis are required to better utilize CO 2 . Metallic Cu, Co, and Ni are widely used as the active species for CO 2 hydrogenation reaction and Cu is especially more beneficial for methanol formation from CO 2 hydrogenation than Co and Ni . However, the catalytic activity of a pure copper catalyst is almost negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, increasing turnover frequencies were observed with increasing Fe particle size for CO hydrogenation (97). Particle size effect of SiO2 supported Ni catalysts on CO2 methanation is also discussed recently (15,98). Vogt et al (15) reported maximum TOF for 2.5nm Ni catalysts, while Chen et.…”
Section: Co2 Methanationmentioning
confidence: 75%
“…al. (98) shows decreasing activity from 2.4 to 4.7nm. Interestingly, both report the highest CO2 methanation activity for catalysts with ~2.4nm particle size.…”
Section: Co2 Methanationmentioning
confidence: 92%